Hot-electron drift velocity in III-V semiconductors under the condition of impact ionization - Singh S.R.; Pal B.B. (My University, 2025)
A calculation has been carried out for the drift velocity of electrons in the highfield region under the condition of impact ionization in III-V semiconductor compounds. The energy-balance equation of the one-electron model has been solved considering alloy scattering and carrier-carrier interaction, in addition to optical phonon and ionization scattering. Fairly good agreement is obtained for GaAs with the available experimental and Monte-Carlo results. Graphs for the high-field drift velocity has also been plotted for Ga1-xInxAs (x = 0.53) at different ratios of ionization mean-free path and optical phonon mean-free path. The plot of high-field drift velocity versus ionization rate reveals that the high-field drift velocity strongly depends on the ionization rate of carriers, and vice versa. © 1987 Springer-Verlag.